CODA: Mobile interface for enabling safer navigation of unmanned aerial vehicles in real-world settings. Issue 145 (January 2021) - Solovey, Erin T.; Ryan, Kimberly J.; Cummings, M.L.
Highlights: Presents the design and empirical study of a mobile Collision and Obstacle Detection and Alerting (CODA) interface for micro-aerial vehicles. The results show improved operator awareness of obstacles and fewer crashes compared to navigation without the CODA interface. The study informs the design of drone systems for safe use with minimal training requirements and facilitates wider adoption of drone technology. Abstract: Recent legislation opening commercial operations to small drones, also known as Micro Aerial Vehicles (MAVs) under 55 lbs, is leading to increased use across many facets of society including first responders, news agencies, commercial entities, and hobbyists. However, the widespread use of such systems will be limited unless a few key hurdles are overcome, namely improved usability and support for safe operation in dynamic environments. To this end, we present the Collision and Obstacle Detection and Alerting (CODA) display, a novel interface that enables safe piloting of MAVs with a mobile device in obstacle-dense real-world settings. We describe the system design, architecture, and development. In addition, we present observations from a proof-of-concept technical demonstration and an empirical study with minimally-trained users. Results showed that CODA reduced collisions and improved operator awareness of obstacle proximity, confidence going around corners and perceived performance in avoiding walls and obstacles.